The Dialectic of Dayak Traditional Rituals of the Balala’ to Prevent the Spread of the COVID-19 in Landak Regency of West Kalimantan Province - Kristianus Kristianus (STKIP Singkawang, 2021)
The background of this research is the occurrence of the COVID-19 pandemic in the world, including in the Landak Regency, West Kalimantan Province. Various efforts had been made by the government, religious institutions, and traditional institutions. Dayak traditional institutions in Landak Regency and all traditional administrators in various Dayak villages in Landak Regency carried out Balala' traditional rituals to prevent transmission. The purpose of this study was to describe the perceptions and reasons for the Dayak indigenous people to carry out the Balala' ritual concerning efforts to prevent the transmission of the COVID-19. This study used a qualitative method, where data was taken by observation, literature study, and interviews. Interviews were conducted by going down the field and also interviews via WhatsApp. The data analysis technique used an interactive model. The results showed that the Balala' ceremony which was held by the Kanayatn Dayak people in the Landak Regency of West Kalimantan, was believed by those who attended it to be able to free them from the attack of this COVID-19 outbreak, because of three things, namely: (1) they had invited Jubata to come on during the Balala' ritual so Jubata would protect them; (2) The traditional Balala' ceremony is in line with the government's call for social distancing; and (3) those who had been Balala' are clean so that the COVID-19 virus cannot enter them. This research needs to be continued especially to see firsthand the effectiveness of the traditional Balala’ ceremony on the transmission of the Covid-19 and the impact of this pandemic on the social, cultural, and economic life of the Dayak indigenous people.